Issues at the Rural-Urban Fringe: The Land Use Debate--Situational Background - Rodney L. Clouser (EDIS)
This fact sheet is one in a series that addresses issues associated with land use at the rural-urban fringe. This fact sheet is designed to explain the background related to land use issues at the rural-urban fringe, conflicts that arise due to growth and use of land, and various methods used throughout the United States to slow the conversion of agricultural land to nonagricultural uses. This is EDIS document FE551, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. This document is one of a series entitled "Issues at the Rural Urban Fringe". Published May 2005.